Effect of La0.7Sr0.3MnO3 crystal structures on magnetization of (1 1 1) oriented La0.7Sr0.3MnO3–SrRuO3 superlattices. (20th April 2016) - Behera, B C; Padhan, P; Prellier, W
Abstract: A series of superlattices consisting of 15 bilayers of ferromagnetic La0.7 Sr0.3 MnO3 (LSMO) and SrRuO3 (SRO) were grown with either stacking order on (1 1 1) oriented SrTiO3 (STO) substrates using the pulsed laser deposition technique. The Raman spectra of these superlattices show the existence of rhombohedral and orthorhombic crystal structures of LSMO in (111)STO/[11-unit cell (u.c.) LSMO/n-u.c. SRO]X15 superlattices with n   =  2 and 3. Interestingly, the Raman spectra of (1 1 1)STO/[11-u.c. SRO/ n -u.c. LSMO]X15 superlattices with n   =  2 and 3 show only the orthorhombic structure of LSMO. The (1 1 1)STO/[11-u.c. LSMO/ n -u.c. SRO]X15 superlattices exhibit enhanced magnetization with weak antiferromagnetic coupling whereas reduced magnetization with strong antiferromagnetic coupling is observed in (1 1 1)STO/[11-u.c. SRO/ n -u.c. LSMO]X15 superlattices. The observed magnetic properties of these superlattices can be explained by the interfacial structural coupling, as evident from their Raman spectra which suggest a modification in the stereochemistry of Mn at the interfaces.